Effect of vegetable residues incorporation on soil fertility, rhizosphere microbial community structure, and plant growth of continuously cropped cucumber in a solar greenhouse - Xiaolu Chen; Dalong Zhang; Xiaoya Li; Xiaotian Li; Jie Lou; Min Wei (Annals of Microbiology, 2022)
Abstract Purpose Incorporating crop residues into the soil is considered a sustainable and valuable method to alleviate soil deterioration caused by continuous monoculture in greenhouse production. However, the effect of vegetable residues retention on soil amendments is poorly understood. In the present study, we investigated the impacts of sweet pepper, tomato, and cucumber plant residues on soil microbial communities and plant growth of continuously cropped cucumber in a solar greenhouse. Methods The 16S rRNA and ITS1 rRNA genes were amplified, and high-throughput sequencing was performed to explore the impacts of vegetable residues incorporation on soil microbial communities. Additionally, soil chemical properties, cucumber root vigor, and fruit yield were measured to assess the impacts of vegetable residues incorporation on continuously cropped soil and cucumber growth. Results The results showed that incorporating vegetable residues could improve soil buffering capacity, increase the content of soil organic matter and available nutrients, and increased the diversity of soil microorganisms and improved community structure; vegetable residues increased the abundance of beneficial bacteria such as Actinobacteria, Firmicutes, Proteobacteria, and Chloroflexi, while reducing the quantity of soil-borne pathogens such as Bacillariophyta and Acidobacteria. Similar results were observed for the fungal communities: the relative abundance of Ascomycota was decreased to varying degrees, while the relative abundance of Rozellomycota and Basidiomycota was raised. The results demonstrated that vegetable residues incorporation significantly increased cucumber root vigor and enhanced fruit yield. The effects of different types of residues on improving soil properties were ordered sweet pepper plant residues > cucumber plant residues > tomato plant residues, and 20% of sweet pepper plant residues incorporation had the most significant effect on crop yield. Conclusion In summary, returning vegetable residues alleviated soil continuous cropping obstacles by improving the soil fertility and the diversity and community structure of soil microorganisms, and consequently promoting the growth and yield of greenhouse-grown cucumbers. The findings demonstrated that returning vegetable residues was an effective and sustainable measure for soil amendment during continuous cropping in greenhouse production.